Controlling the particle size and pore size of mesoporous SiO2 nanoparticles for enhanced drug loading efficiency - Linh, Pham Hoai; Huong, Tran Thi; Nhung, Nguyen Hong; Dung, Nguyen Quoc; Bach, Ta Ngoc; Anh, Nguyen Thi Ngoc; Nam, Nguyen Thanh; Fedotova, Julia A.; Dung, Nguyen Tien (Vietnam Journal of Science and Technology, 2025)
In this work, we focus on synthesizing mesoporous SiO2 nanoparticles (NPs) with various sizes and pore sizes for enhancing BET surface area to apply in drug delivery by a simple modified Stöber method. By adjusting the ethanol content in the solvent mixture of cetyltrimethylammonium bromide (CTAB), four samples with particle sizes in a range of 50 nm to 350 nm and with average pore size in a range of 2.72 nm to 8.29 nm were obtained. The SiO2 NPs exhibit a mesoporous structure with an amorphous phase, and perfect spherical morphology. The N2 adsorption-desorption analysis reveals that mesoporous SiO2 NPs display high BET surface values, which depend strongly on the synthesis condition as well as the particle diameters and pore sizes. The BET values increase from 848 m2/g to 1019 m2/g when the ethanol content in the solvents decreases from 20 % to 10 %. The Doxorubicin (DOX) loading properties were investigated as well. The highest amount of loaded DOX was achieved with 98 % loading efficiency as 99 μg/mg for the SiO2 NPs with smallest size. The results suggest that the high surface mesoporous SiO2 has great potential in drug delivery applications.